Predictive factors related to the progression of periodontal disease in patients with early rheumatoid arthritis: a cohort study - Ana María Heredia-P; Gloria Inés Lafaurie; Wilson Bautista-Molano; Tamy Goretty Trujillo; Philippe Chalem-Choueka; Juan M Bello-Gualtero; Cesar Pacheco-Tena; Lorena Chila-Moreno; Consuelo Romero-Sánchez (BMC, 2019)
Abstract Background Rheumatoid arthritis (RA) and periodontal disease are inter-related conditions. However, factors predictive of periodontal disease progression in patients with early rheumatoid arthritis (eRA) are lacking. The aim of this study was to identify factors associated with the progression of clinical attachment loss (CAL) in interproximal dental sites of eRA patients. Methods Twenty-eight eRA patients were evaluated for the progression of CAL at 280 interproximal dental sites at 1 year of follow-up. Markers of RA activity (rheumatoid factor, erythrocyte sedimentation rate, and C-reactive protein), a marker of bone resorption (Dickkopf-related protein 1), Disease Activity Score 28 and Simple Disease Activity Index were included as potential systemic predictive factors. Plaque index, gingival index, pocket depth, clinical attachment level and Dickkopf-related protein 1 in crevicular fluid at baseline were included as potential local predictive factors. Data were analysed in a hierarchical structure using generalised linear mixed models for progression at each site (> 2 mm) during follow-up. Results C-reactive protein level was the most important predictive systemic factor for the progression of CAL. The mean CAL and a high degree of gingival inflammation in interproximal sites at baseline were important predictive local factors (p <  0.0001). Patients who received combined treatment with disease-modifying antirheumatic drugs and corticosteroids exhibited less CAL (p <  0.0001). The predictive value of the generalised linear mixed model for progression was 85%. Conclusions Systemic factors, including RA disease activity and baseline periodontal condition, were associated with periodontal progression. Pharmacological treatment may affect periodontal progression in patients with early RA.